(untitled) (Nigerian Journal of Technology, 2015)
The study of the effect of barrel temperatures on the tensile strength, proof stress, percentage elongation and flexural modulus of injected moulded plastic products of polyvinyl chloride (PVC), polypropylene (PP) and high density polyethylene (HDPE) have been carried out. An existing mould was used for the production of tension and deflection test specimen. Then a plunger type of injection machine was used to mould test specimens at various barrel temperatures ranging from 1600C to 2800C, keeping all other process variables constant. The tensile and deflection test carried out on the specimen, The results obtained showed that the maximum tensile strength for PVC, PP, and HDPE are 6.10N/mm2, 21.67N/mm2, and 12.94N/mm2 at barrel temperature of 2700C, 2700C, 2100C; Maximum proof stress was 3.44N/mm2, 20.63N/mm2, and 13.65N/mm2 at barrel temperature of 2400C, 2500C and 1600C; Maximum percentage elongation was 281% , 172%, and 313% at barrel temperature of 2700C, 2700C, and 2300C and Maximum flexual modulus was 19.56 X102 N/mm2, 29.03 X102 N/mm2 and 27.88 X102 N/mm2 at barrel temperatures of 2400C, 2800C, and 1600C respectively. http://dx.doi.org/10.4314/njt.v34i2.12